Biofilms Formed by Gram-Negative Bacteria Undergo Increased Lipid A Palmitoylation, Enhancing In Vivo Survival - Sabina Chalabaev (American Society for Microbiology, 2014)
ABSTRACT Bacterial biofilm communities are associated with profound physiological changes that lead to novel properties compared to the properties of individual (planktonic) bacteria. The study of biofilm-associated phenotypes is an essential step toward control of deleterious effects of pathogenic biofilms. Here we investigated lipopolysaccharide (LPS) structural modifications in Escherichia coli biofilm bacteria, and we showed that all tested commensal and pathogenic E. coli biofilm bacteria display LPS modifications corresponding to an increased level of incorporation of palmitate acyl chain (palmitoylation) into lipid A compared to planktonic bacteria. Genetic analysis showed that lipid A palmitoylation in biofilms is mediated by the PagP enzyme, which is regulated by the histone-like protein repressor H-NS and the SlyA regulator. While lipid A palmitoylation does not influence bacterial adhesion, it weakens inflammatory response and enhances resistance to some antimicrobial peptides. Moreover, we showed that lipid A palmitoylation increases in vivo survival of biofilm bacteria in a clinically relevant model of catheter infection, potentially contributing to biofilm tolerance to host immune defenses. The widespread occurrence of increased lipid A palmitoylation in biofilms formed by all tested bacteria suggests that it constitutes a new biofilm-associated phenotype in Gram-negative bacteria. IMPORTANCE Bacterial communities called biofilms display characteristic properties compared to isolated (planktonic) bacteria, suggesting that some molecules could be more particularly produced under biofilm conditions. We investigated biofilm-associated modifications occurring in the lipopolysaccharide (LPS), a major component of all Gram-negative bacterial outer membrane. We showed that all tested commensal and pathogenic biofilm bacteria display high incorporation of a palmitate acyl chain into the lipid A part of LPS. This lipid A palmitoylation is mediated by the PagP enzyme, whose expression in biofilm is controlled by the regulatory proteins H-NS and SlyA. We also showed that lipid A palmitoylation in biofilm bacteria reduces host inflammatory response and enhances their survival in an animal model of biofilm infections. While these results provide new insights into the biofilm lifestyle, they also suggest that the level of lipid A palmitoylation could be used as an indicator to monitor the development of biofilm infections on medical surfaces.